Yucatan Minipig Knee Meniscus Regional Biomechanics and Biochemical Structure Support its Suitability as a Large Animal Model for Translational Research - Gonzalez-Leon, Erik A.; Hu, Jerry C.; Athanasiou, Kyriacos A. (Frontiers in Bioengineering and Biotechnology, 2022)
Knee meniscus injuries are the most frequent causes of orthopedic surgical procedures in the U.S., motivating tissue engineering attempts and the need for suitable animal models. Despite extensive use in cardiovascular research and the existence of characterization data for the menisci of farm pigs, the farm pig may not be a desirable preclinical model for the meniscus due to rapid weight gain. Minipigs are conducive to in vivo experiments due to their slower growth rate than farm pigs and similarity in weight to humans. However, characterization of minipig knee menisci is lacking. The objective of this study was to extensively characterize structural and functional properties within different regions of both medial and lateral Yucatan minipig knee menisci to inform this model’s suitability as a preclinical model for meniscal therapies. Menisci measured 23.2-24.8mm in anteroposterior length (33-40mm for human), 7.7-11.4mm in width (8.3-14.8mm for human), and 6.4-8.4mm in peripheral height (5-7mm for human). Per wet weight, biochemical evaluation revealed 23.9-31.3% collagen (COL; 22% for human) and 1.20-2.57% glycosaminoglycans (GAG; 0.8% for human). Also, per dry weight, pyridinoline crosslinks (PYR) were 0.12-0.16% (0.12% for human) and, when normalized to collagen content, reached as high as 1.45-1.96ng/µg. Biomechanical testing revealed circumferential Young’s modulus of 78.4-116.2MPa (100-300MPa for human), circumferential ultimate tensile strength (UTS) of 18.2-25.9MPa (12-18MPa for human), radial Young’s modulus of 2.5-10.9MPa (10-30MPa for human), radial UTS of 2.5-4.2MPa (1-4MPa for human), aggregate modulus of 157-287kPa (100-150kPa for human), and shear modulus of 91-147kPa (120kPa for human). Anisotropy indices ranged from 11.2-49.4 and 6.3-11.2 for tensile stiffness and strength (approximately 10 for human), respectively. Regional differences in mechanical and biochemical properties within the minipig medial meniscus were observed; specifically, GAG, PYR, PYR/COL, radial stiffness, and Young’s modulus anisotropy varied by region. The posterior region of the medial meniscus exhibited the lowest radial stiffness, which is also seen in humans and corresponds to the most prevalent location for meniscal lesions. Overall, similarities between minipig and human menisci support the use of minipigs for meniscus translational research.